Effectiveness of Lymphedema Prevention Programs With Compression Garment After Lymphatic Node Dissection in Breast Cancer: A Randomized Controlled Clinical Trial - Nadal Castells, Maria J.; Ramirez Mirabal, Eliot; Cuartero Archs, Jordi; Perrot Gonzalez, Jean C.; Beranuy Rodriguez, Marta; Pintor Ojeda, Alberto; Bascuñana Ambros, Helena (Frontiers in Rehabilitation Sciences, 2021)
ABSTRACT Objective: Patients with breast cancer who undergo axillary lymph node dissection (ALND) are at risk of developing lymphedema, which can negatively impact quality of life. Lymphedema prevention programs, which primarily consist of educational content and exercise, have been shown to reduce the incidence of lymphedema. The addition of compression garments (CG) may increase the effectiveness of these programs. We conducted a randomized clinical trial (RCT) to determine whether adding CG to a conventional lymphedema prevention program could improve treatment effectiveness. Methods: Seventy patients who had undergone ALND for breast cancer were randomized to receive conventional preventative therapy (control arm, n=35) consisting of a one-hour educational session and a 12-week exercise program or the same therapy plus upper limb CGs (experimental arm, n=35). Patients in the experimental arm were instructed to wear the CG ≥ 8 hours/day for the first three months after surgery and 2 hours/day thereafter. Results: At two-years, the overall incidence of lymphedema in the two groups was 12.3%, with no significant differences between the conventional and experimental arms (12.5% vs. 12.1%). In the experimental arm, the incidence of lymphedema was significantly lower (p=0.02) in patients who used the CGs daily as recommended compared to patient who did not adhere to this treatment recommendation. Neither exercise (p=0.518) nor education alone decreased the incidence of lymphedema. Adherence decreased over time. Conclusions: The findings of this RCT show that health education, preventive exercise programs, and patient adherence to therapeutic recommendations all play an important role in preventing lymphedema. This study shows that the use of a compression garment during the first three months after axillary node dissection may reduce the likelihood of lymphedema in high-risk patients.